2017
DOI: 10.7324/japs.2017.70632
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and biological effects of Caffeine on substrate metabolism homeostasis: A systematic review

Abstract: Objective: This review aims to elucidate the possible effects of caffeine over homeostasis mechanism of energetic subtracts metabolism. Methods: The study was carried out in systematic review form and its sample comprised six scientific papers published in academic journals. Only the studies involving soccer players (professionals and amateurs, except goalkeepers) were included in this review. Results: Caffeine was able to increase insulin and serum glycemia levels, after oral glucose tolerance test (OGTT), de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Caffeine is a major active component of green tea and coffee, but the synergistic effects of caffeine with catechins and chlorogenic acid were not considered in this study. While caffeine consumption may improve glucose tolerance, its effect on glucose levels varies among studies [ 37 ]. On the other hand, several studies report that caffeine consumption increases insulin secretion, but does not necessarily improve glucose levels in oral glucose tolerance tests [ 38 , 39 , 40 ], suggesting that caffeine influences insulin clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine is a major active component of green tea and coffee, but the synergistic effects of caffeine with catechins and chlorogenic acid were not considered in this study. While caffeine consumption may improve glucose tolerance, its effect on glucose levels varies among studies [ 37 ]. On the other hand, several studies report that caffeine consumption increases insulin secretion, but does not necessarily improve glucose levels in oral glucose tolerance tests [ 38 , 39 , 40 ], suggesting that caffeine influences insulin clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the thermal response in different thermal windows and on the RT of piglets, the progressive increases in OCU, EAR, NOSE, LIMB, and RT are due to caffeine boosting basal metabolism by interacting with adenosine receptors in the sympathetic nervous system [63]. Jarrat et al [10] mentions that raising metabolic activity in newborn piglets that have limited energy resources at birth can help them increase body temperature [13].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the antagonism of A 2A ARs is expected to oppose these actions, and hence, reduce insulin resistance and glucose output from the liver. A recent study also indicated that caffeine stimulates A 2A ARs and triggers glycogenesis in the liver [ 46 ]. Interestingly, the dual A 1 /A 2A AR antagonists, 2-BI and caffeine, and the selective A 2A AR antagonist, istradefylline, demonstrated an improved anti-hyperglycemic activity compared to metformin and pioglitazone.…”
Section: Discussionmentioning
confidence: 99%